JustCookies ordering mobile application with notification / Muhammad Danial Mohd Amin - Mohd Amin, Muhammad Danial (2021)
The project objectives will focus on to gather and analyse the requirements, design based on analyses requirement and to develop a JustCookies Ordering Mobile Application With Notification. The aim of this project is to develop JustCookies Ordering Mobile Application with Notification to monitor and control the order process of JustCookies. The development is motivated due to the difficulty in managing many platforms used in receiving customer orders, difficulty to search for specified order from customers and problem in keeping track on the time and date of delivery. To develop the mobile application a modified waterfall model is applied. The modified waterfall consists of three development phases; requirements gathering and analysis followed by design and the implementation phase. (what is modified?). In requirements gathering and analysis phase, the deliverables from the activities are documented in Software Requirement Specification (SRS). For design phase, the deliverables such as all the design diagrams, the interface of system in storyboard are documented in Software Design Document (SDD). Finally, in implementation phase a functional JustCookies Ordering Mobile Application with Notification is developed. With the mobile application as the platform, ordering is made easier for the customers and for the owner, Mr. Zainul to receive the cookie orders from the customers. The order process is more organized and easily managed and tracked. Additions to improve the apps in the future include online payment and a chatbot feature into the application of JustCookies as a medium of communication between seller and customer as well as customer and customer.